The BAF45D Protein Is Preferentially Expressed in Adult Neurogenic Zones and in Neurons and May Be Required for Retinoid Acid Induced PAX6 Expression - Liu, Chao; Sun, Ruyu; Huang, Jian; Zhang, Dijuan; Huang, Dake; Qi, Weiqin; Wang, Shenghua; Xie, Fenfen; Shen, Yuxian; Shen, Cailiang (Frontiers in Neuroanatomy, 2017)
Adult neurogenesis is important for the development of regenerative therapies for human diseases of the central nervous system (CNS) through the recruitment of adult neural stem cells (NSCs). NSCs are characterized by the capacity to generate neurons, astrocytes, and oligodendrocytes. To identify key factors involved in manipulating the adult NSC neurogenic fate thus has crucial implications for the clinical application. Here, we report that BAF45D is expressed in the subgranular zone (SGZ) of the dentate gyrus, the subventricular zone (SVZ) of the lateral ventricle, and the central canal (CC) of the adult spinal cord. Coexpression of BAF45D with glial fibrillary acidic protein (GFAP), a radial glial like cell marker protein, was identified in the SGZ, the SVZ and the adult spinal cord CC. Quantitative analysis data indicate that BAF45D is preferentially expressed in the neurogenic zone of the LV and the neurons of the adult CNS. Furthermore, during the neuroectoderm differentiation of H9 cells, BAF45D is required for the expression of PAX6, a neuroectoderm determinant that is also known to regulate the self-renewal and neuronal fate specification of adult neural stem/progenitor cells. Together, our results may shed new light on the expression of BAF45D in the adult neurogenic zones and the contribution of BAF45D to early neural development.